A Not So New Basis for Animal Ethics: Review of Bernie Rollin, A New Basis for Animal Ethics: Telos and Common Sense - Everett, Jennifer (Humanimalia, 2018)
Bernie Rollin, A New Basis for Animal Ethics: Telos and Common Sense. University of Missouri Press, 2016. 209 pp. 40.00.